Evaluation Of Dexmedetomidine As An Adjuvant To Epidural Bupivacaine In Vaginal Hysterectomy - Pratiksha, Chitta; Saraiah, Rontala; Saraswathi, V. Sai; M, Gouthami (Journal of Neonatal Surgery, 2025)
Background: Effective perioperative pain management is crucial for patient recovery and satisfaction. This study evaluates the efficacy of dexmedetomidine as an adjuvant to epidural bupivacaine in vaginal hysterectomy procedures. Methods: Sixty patients aged 30–60 years, classified as ASA physical status I or II, scheduled for vaginal hysterectomy under epidural anesthesia were randomized into two groups. Group A received 15 mL of 0.5% bupivacaine epidurally, while Group B received the same plus dexmedetomidine 0.5 µg/kg. Onset times of sensory and motor blockade, levels of maximum sensory blockade, duration of analgesia, and recovery parameters were recorded. Hemodynamic parameters and sedation levels were monitored intraoperatively and postoperatively. Results: Group B demonstrated a significantly faster onset of sensory blockade (10.14 ± 2.94 min) compared to Group A (17.12 ± 2.44 min; p < 0.001). Higher levels of maximum sensory blockade were achieved in Group B, with 76.7% reaching T4 level. The duration of analgesia was significantly longer in Group B (320.8 ± 31.5 min) versus Group A (173.4 ± 16.1 min; p < 0.001). Recovery times for sensory and motor blockade were also prolonged in Group B without significant adverse effects. Sedation levels were higher in the dexmedetomidine group, enhancing patient comfort. Conclusion: Dexmedetomidine as an adjuvant to epidural bupivacaine improves anesthetic efficacy and prolongs analgesia in vaginal hysterectomy patients. Its use is associated with faster onset, higher sensory blockade levels, extended analgesia, and increased patient comfort without significant hemodynamic instability.